OVERVIEW OF CHARACTERISTIC OWNERSHIP OF HEALTHY INSIGHTS: A STUDY OF THE COMMUNITIES IN KELURAHAN KEDOYA SELATAN, INDONESIA - Nitami, Mayumi; Kristina Letek, Maria; Puspitaloka Mahadewi, Erlina; Nurohmah, Hety (International Journal of Psychosocial Rehabilitation, 2020)
WHO refers sanitation as the provision of facilities and services for the disposal of human waste such as urine. Poor sanitation conditions will have a negative impact on many aspects of life starting from the decline in the quality of the environment, pollution of drinking water sources, increasing the number of diarrhea and the emergence of several diseases. The purpose of this research is knowing Description of the characteristics of unhealthy latrine ownership in the community RT 01/RW 05 Kedoya Selatan District year 2019. The study used a cross sectional design with a simple random sampling technique, with 51 samples from a population of 131 families. Data were analyzed by univariate and bivariate using the chi-square test. The results of this study were obtained with good knowledge 75,5%, good attitude 39,2%, higher education 35,3%, high economic status 23,5%, support from supporting community leaders 88,2%. Health workers need to collaborate with the Kedoya Kelurahan government to provide direction for the community through counseling containing budgeting from village funds to build healthy latrines, especially the construction of joint septic tanks for low-income communities.